Improving the competency-based training model based on digital platforms in the vocational education system - Sherzod Toshpulatov (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
Abstract. This thesis analyzes the issues of improving the competency-based training model based on digital platforms in the vocational education system from a scientific, theoretical and practical perspective. It is substantiated that in the context of digital transformation processes, fundamental changes are taking place in the content, form and methods of the education system, especially the need to introduce modern digital technologies in vocational education is increasing.